Propelling diverse leaders to the top: A developmental network approach - Chanland, Dawn E.; Murphy, Wendy Marcinkus (Human Resource Management, 2018)
Scholars and practitioners are making a strong business case for greater representation of women and other underrepresented groups on senior management teams and boards. A model is developed that highlights how to create optimal developmental networks—groups of developers who help advance people's careers and personal growth—that can assist in propelling diverse leaders into the upper echelons of their organizations and board positions. Several literature streams are integrated in order to identify developmental networks that will help diverse leaders overcome barriers to breaking the glass ceiling in greater numbers. Numerous strategies intended to shape diverse leaders' network structure and content are discussed, as are contextual challenges that may inhibit optimal networks' development. Lastly, theoretical and practical implications for individuals and organizations are highlighted.